2011
DOI: 10.1242/jeb.057554
|View full text |Cite
|
Sign up to set email alerts
|

Social synchronization of circadian locomotor activity rhythm in the fruit fly Drosophila melanogaster

Abstract: SUMMARYSupplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(45 reference statements)
2
16
0
Order By: Relevance
“…Our study shows that olfaction plays a vital role in SSI, which is consistent with the findings of previous studies which have also implicated the role of olfaction in mediating social signals during social interactions particularly those that are sexual in nature [11][15], [28]. However, we do not know yet whether reduction of the evening activity peak in SSI males is merely a residual effect of SSI, or whether it has an adaptive significance for males to be less active during peak mating time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study shows that olfaction plays a vital role in SSI, which is consistent with the findings of previous studies which have also implicated the role of olfaction in mediating social signals during social interactions particularly those that are sexual in nature [11][15], [28]. However, we do not know yet whether reduction of the evening activity peak in SSI males is merely a residual effect of SSI, or whether it has an adaptive significance for males to be less active during peak mating time.…”
Section: Discussionsupporting
confidence: 93%
“…These studies suggest that fruit flies can convey temporal information by socially interacting with each other. However, social cycles were unable to entrain the circadian clocks of D. melanogaster , although they had significant impact on the phase of circadian locomotor activity rhythm [14], [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same conclusion was also reached by Fujii and co-workers [16], although they only examined the behaviors of WT flies after couples were separated. In grouped male flies, individual activity rhythms have a synchronized phase [5,40]. Importantly, the effect of the phase synchronization decreases with group size.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that cell-cell communication could act on the repression of Bmal1 transcription to stabilize circadian cycling. As in the case of fruitflies of mixed genetic backgrounds [12,16], and honeybees in a colony [29], the rhythmic phenotype of an individual can be altered by interaction with other oscillating individuals.…”
Section: Suprachiasmatic Nucleus and The Synchrony Of Cellular Circadmentioning
confidence: 99%